Economic Integration And Environment In Organizing Ports Services (Management Of Juridical Analysis Of Tanjung Emas Port In Semarang) - Widya Putri Idayatama; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The study